2017
DOI: 10.5569/2340-5104.05.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Accesibilidad universal: sentido normativo e implicaciones en la educación y la práctica profesional

Abstract: Para citar:Aparicio, M. y Martínez Navarro, E. (2017): "Accesibilidad universal: sentido normativo e implicaciones en la educación y la práctica profesional". ResumenEn la Convención sobre los Derechos de las Personas con Discapacidad, aprobada por la ONU en 2006, se incluye el derecho a la accesibilidad universal y el diseño para todas las personas. En este trabajo nos ocupamos, en primer lugar, de clarificar el sentido normativo que tiene este derecho. Posteriormente, analizamos sus implicaciones en el ámbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…The study has found that, although a significant part of the school textbooks researched is changing the way diversity is treated, graphic representation of cultural and functional diversity is still insufficient, partial, plain and fragmented. In the case of gender, consistent with recent literature (Martens, 2015;Aparicio, & Martínez, 2017), there are elements of parity included in textbooks representations in the public and private spheres; women and girls are performing activities and developing jobs that are traditionally not considered female one, and the same goes for men and boys. These findings are extremely encouraging as they are a reflection of the construction of a gender-fair society or, at least with the commitment of moving towards one.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The study has found that, although a significant part of the school textbooks researched is changing the way diversity is treated, graphic representation of cultural and functional diversity is still insufficient, partial, plain and fragmented. In the case of gender, consistent with recent literature (Martens, 2015;Aparicio, & Martínez, 2017), there are elements of parity included in textbooks representations in the public and private spheres; women and girls are performing activities and developing jobs that are traditionally not considered female one, and the same goes for men and boys. These findings are extremely encouraging as they are a reflection of the construction of a gender-fair society or, at least with the commitment of moving towards one.…”
Section: Discussionsupporting
confidence: 65%
“…Regarding functional diversity, the Convention on the Rights of Persons with Disabilities (United Nations, 2006) recognizes the right to universal accessibility and design for all users, implying the need to strengthen disabled people's social participation. The adoption of this Convention implies the recognition and commitment of institutional policies to the promotion of accessibility and the achievement of a more inclusive society (Aparicio & Martínez, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Para potenciar la inclusión educativa, dándole un sentido más amplio al colectivo de estudiantes en general, cobra importancia el diseño de los procesos formativos bajo los principios del diseño universal de aprendizaje (DUA) (Ferrer et al, 2011). Cuando las instituciones educativas adoptan este enfoque, tanto los productos como los entornos se diseñan para que sean usados por todas las personas sin necesidad de generar ninguna adaptación o diseño específico (Aparicio y Martínez, 2017;Aparicio y Rodríguez, 2020;Cotán, 2017;Perera-Rodríguez y Moriña, 2019;Preiser y Smith, 2011;Powell, 2013). Consecuentemente, el diseño universal de los productos digitales garantiza que los requisitos establecidos en la accesibilidad (percepción, compresión e interacción) se cumplan (Horton y Leventhal, 2008).…”
Section: Introductionunclassified